Al-Išārah Wa Al-'Ibārah Wa Aṯaruhā Fi Taḥdīd Al-Muṣṭalaḥāt Al-Ṣūfiyyah: The Sign, The Phrase, And Its Impact On The Definition Of Sufi Terms / الإشارة والعبارة وأثـرها في تحديد المصطلحات الصوفية - Nur Hadi Ihsan; Muhammad Ishommudin (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2020)
This study will analyze the use of the 'al-Isyārah' and 'al-Ibārah' diction in the perspective of Sufi expressions of Ibn Athāillah as-Sakandary, as well as analyze the influence of the language on the technical terms in the discipline of Sufism. Ulama have criticized the technical term used by Sufis in their books from other fields because Sufis use technical terms that are rarely used and seem strange. Sufis prefer a cryptic language called 'isyārah,' but in some cases, they also use an explicit language commonly called al-Ibārah.' Ibn Athāillah (d. 709 h) has an interesting description of this topic and places it proportionally. Both ‘isyārah’ and ‘ibārah’ are a form of a method for expressing intuitive knowledge about the secrets of God. ' al-Ibārah' can be used if a Sufi does have specific capabilities. Also, it can be used as a form of education for the sālik. Apart from these two things, a Sufi can express it with 'al-Isyārah' and 'rumziyyah' or choose to store it as personal knowledge. The way this disclosure impacts the technical terms used. Sufis choose metaphorical or technical expressions that differ from philosophical, kalam, or tasawuf traditions. Thus, despite using such words, their technical time does not come out of the scientific standard.